(untitled) (Academicia Review-A Multidisciplinary Online Journal, 2026)
Brain abscess is a focal intracerebral infection of the central nervous system that requires prompt diagnosis and comprehensive medical management. This review analyzes the epidemiology and pathogenesis of brain abscess, clinical and neurological manifestations, modern neuroimaging and laboratory diagnostic methods, as well as principles of differential diagnosis and therapeutic strategies including antibiotic therapy and neurosurgical interventions. Particular attention is given to the diagnostic value of magnetic resonance imaging and diffusionweighted imaging